2013
DOI: 10.1521/jscp.2013.32.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Ignoring Norms with a Little Help from my Friends: Social Support Reduces Normative Influence on Drinking Behavior

Abstract: Alcohol norms are strong predictors of drinking. However, the extent to which norms influence behavior depends on how closely people attend to them; people are more likely to attend to norms when their affiliation needs are unfulfilled by members of their social networks (Cullum, O'Grady, & Tennen, 2011). Therefore, we predicted that Perceived Social Support (PSS) would moderate the relationship between norms and drinking such that people with low levels of PSS would be more motivated to attend to norms. Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
3
15
0
1
Order By: Relevance
“…The emphasis on friends taking care of friends is consistent with findings on the significant influence that friends can have on a wide range of individuals’ health-related behaviors (e.g. Cullum, O’Grady, Sandoval, Armeli, & Tennan, 2013; Fitzgerald, Fitzgerald, & Aherne, 2012; Lau, Quadrel, & Hartman, 1990). In addition, there are developmental as well as empirically-based reasons to believe that encouraging students to take action to protect friends, as compared to generalized “others,” would contribute to successful intervention effects (e.g., Levine, Cassidy, Brazier, & Reicher, 2002).…”
Section: Sexual Violence Prevention Programs On College Campusessupporting
confidence: 83%
“…The emphasis on friends taking care of friends is consistent with findings on the significant influence that friends can have on a wide range of individuals’ health-related behaviors (e.g. Cullum, O’Grady, Sandoval, Armeli, & Tennan, 2013; Fitzgerald, Fitzgerald, & Aherne, 2012; Lau, Quadrel, & Hartman, 1990). In addition, there are developmental as well as empirically-based reasons to believe that encouraging students to take action to protect friends, as compared to generalized “others,” would contribute to successful intervention effects (e.g., Levine, Cassidy, Brazier, & Reicher, 2002).…”
Section: Sexual Violence Prevention Programs On College Campusessupporting
confidence: 83%
“…Fourth, we chose to emphasize the notion of friends taking care of friends because friends have an important influence on a wide range of health-related behaviors (e.g. Cullum, O’Grady, Sandoval, Armeli, & Tennan, 2013; Fitzgerald, Fitzgerald, & Aherne, 2012; Lau, Quadrel, & Hartman, 1990). In addition, there is some research indicating that individuals may be more inclined to take action and intervene to protect a friend, as compared to intervening to protect a stranger or acquaintance (e.g., Levine, Cassidy, Brazier, & Reicher, 2002).…”
mentioning
confidence: 99%
“…Finally, research on the effects of social exclusion has provided evidence that experiencing (or reliving) exclusion leads to thwarted belonging needs which, in turn, increase an individual's susceptibility to social influence (see Blackhart, Nelson, Knowles, & Baumeister, ; Gerber & Wheeler, , for meta‐analytic reviews on the effects of social exclusion). For instance, Carter‐Sowell, Chen, and Williams () found that ostracized individuals tended to comply more often with a request to donate money than did members of a control group (e.g., Cullum, O'Grady, Sandoval, Armeli, & Tennen, ; Watson‐Jones, Whitehouse, & Legare, ). Consistent with that, excluded (vs. non‐excluded) individuals showed a higher tendency to affiliate with the ingroup by mimicking a confederate who was an ingroup member (Lakin, Chartrand, & Arkin, ).…”
Section: Loyal Deviance As a Function Of Ingroup Identification And Pmentioning
confidence: 99%